TANGGUNG JAWAB HUKUM DOKTER YANG MELAKUKAN MALPRAKTEK KEPADA PASIEN PASCA OPERASI CAESAR (STUDI PUTUSAN NO. 484PDT.G2013PN. JKT. SEL.) - Prasetyanov, Yudha; Mene, Meydianto (Ensiklopedia of Journal, 2025)
Abstract: This article examines the criminal liability of doctors committing malpractice after a cesarean section, using Case No. 484/Pdt.G/2013/PN. Jkt. Sel. as a study. The research applies a normative juridical approach with responsive legal analysis, justice theory, and professional ethics. Findings indicate that the doctor is liable under the fault liability principle, while the hospital and its owner share collective and joint liability due to supervisory negligence. Medical malpractice not only causes legal consequences but also brings normative and moral implications by violating patients' rights and undermining public trust. Therefore, medical oversight reform, reinforcement of professional ethics, and clarity in liability allocation within judicial decisions are needed to ensure justice for victims.Keywords: Medical Malpractice, Legal Liability.